"Bad enough governance": state capacity and quality of institutions in post-Soviet autocracies. Issue 2 (3rd March 2016) - Melville, Andrei; Mironyuk, Mikhail
Abstract : This article contributes to current discussions on state capacity, quality of institutions, and political regimes. Our analysis demonstrates that the J-curve argument ("good institutions" in autocracies as compared to hybrid and transitional regimes) may not be generic and is not well supported by empirical evidence from the sample of post-Soviet countries. An explanatory model of the "King of the Mountain" is instead provided. Its focus is on the monopoly of political rent as a precondition for extraction of economic rent. It demonstrates an inverse correlation between the quality of institutions and the extraction of political and economic rent, and explains why an autocrat may not have an incentive to improve institutions that may make his/her monopoly vulnerable, and rather would prefer to preserve a low quality of institutions and "bad enough governance." An analysis of a variety of external and domestic factors that may endanger this monopoly is provided. Finally, the autocrat's alternative strategic choices are analyzed. It is argued that better payoffs for the autocrat – paradoxically – may result from partial reforms and improvement of the quality of institutions. However, for various reasons, this is not occurring in post-Soviet autocracies.